The Effect of Different Beverages on the Microhardness of UltraSeal XT® Hydro: An In Vitro Study. - Alhazmi, Hesham. (2017)
Abstract: Aim The aim of this study is to evaluate the influence of different beverages on the microhardness of UltraSeal XT® hydro. Materials and Methods Samples of the resin sealants were prepared and immersed in milk, Coca-Cola, orange juice, Gatorade, or, as control groups, in artificial saliva and samples without immersion. Specimens were divided into six groups by beverage type (n = 10 per group). Specimens were then immersed in the beverage for 14 days. An indenter was used to perform the Vickers microhardness test on the surface of the resin sealants. Three indentations were performed under a load of 200 g for 15 s. A specimen was selected from each group for qualitative scanning electron microscope assessment. Results The median (inter-quartile range) microhardness for the saliva group was 59.6 (1.2) VHN; for the orange juice group 56.0 (1.1) VHN; for the Coca-Cola group 51.1 (0.9) VHN; for the Gatorade group 52.7 (0.9) VHN; for the milk group 61.4(1.8) VHN; and for the group of specimens that not immersed in any solution 63.9 (3.1) VHN. Groups that showed statistically significant differences were: Coca-Cola-saliva, Coca-Cola-milk, Coca-Cola-not immersed, Gatorade-milk, Gatorade-not immersed, and orange juice-not immersed. Differences were not statistically significant for the other comparison groups. Conclusion Within the limitations of this study and based on the results, the microhardness of UltraSeal XT® hydro decreased more after exposure to beverages with the lowest pH level. Coca-Cola, Gatorade, and orange juice had the greatest effect on the microhardness.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Pediatric Dentistry.; Advisor: Cheen Loo.; Committee: Yoon Kang, Matthew Finkelman, and Gerald Swee.; Keyword: Dentistry.